Inheritance of white rust resistance in Indian mustard - and P. KUMAR, O.P. YADAV*, T.P. YADAVA (Indian Phytopathology, 2002)
The ten Indian mustard [Brassica juncea (L.) Czern & Coss] lines differing in degree of resistance to white rust [Albuga candida (Lav) Kuntze] were crossed in all possible combinations to study the genetic control of white rust resistance. The additive gene effects played a predominant role in the inheritance. The lines EC 126743, EC 126745, Domo-4 and EC 126746-1 were identified as potential parents to transfer disease resistance. Pooled analysis over environments revealed the importance of combining ability 00 environment interaction and emphasized the need for testing over more than one environment for precise estimation of combining ability. Pedigree and bulk methods of selection have been advocated to improve for white rust resistance.